Effects Of Partial Replacement Of Natural Aggregate By Recycled Aggregate From Asphalt Pavement On Properties Of Concrete - Shubandrio, Farid Aizuddin (Universiti Sains Malaysia, 2018)
Recycled asphalt pavement (RAP) can be referred as waste materials that is reclaimed and reprocessed to acquire the asphalt and aggregate. Most of the application of RAP is to be recycled back into pavement and thus, the suitability of the recycled aggregate from asphalt pavement to be used in other possible applications such as Portland cement concrete is not yet being determined. In this study, the effects of partial replacement of coarse aggregate by recycled aggregate from asphalt pavement on properties of concrete has been investigated. The recycled aggregate used was originated from asphalt pavement or recycled asphalt pavement (RAP) aggregate. RAP coarse aggregate was being obtained from JKR Penang and later been crushed into rubbles. The aggregate rubbles sieved and graded to sizes similar as natural crushed granite aggregate. Six concrete mixes with different percentage replacement were made from RAP coarse aggregate. Several tests were conducted including the assessment of physical and mechanical properties of RAP aggregate, as well as physical and mechanical properties of concrete containing RAP aggregate. The results are compared with natural crushed granite aggregate and concrete containing 100% natural crushed granite aggregate as the control mix. For the characterization of the RAP aggregate, the bituminous contaminant found on the surface of the aggregate has greatly influence its physical performance while its mechanical properties are affected by axle loads subjected during its service period as asphalt pavement. For the effects of RAP aggregate on properties of concrete, in terms of physical and mechanical properties, concrete mix with 30% RAP aggregate replacement has been identified as the best mix proportion in all aspects studied.